Screening Marker Components Of Tyrosinase Inhibitor From Xylocarpus Granatum Stem - Latifah K Darusman; Irmanida Batubara; Catharina Lopolisa (Syarif Hidayatullah State Islamic University, 2011)
The aim of our research was to screen the marker components of tyrosinase inhibitor from Xylocarpus granatum stem collected from Pulau Sebuku, South Kalimantan, Indonesia. The screening method started from selection of part of X. granatum, stem or stem bark. Stem and stem bark of X. granatum were dried and grounded before submitted to methanol. The stem extracts is more potent as tyrosinase inhibitor (IC50 for monophenolase is 45.12 μg/ml and diphenolase is 31.59μg/ml) compared to the bark extracts. The IC50 values of kojic acid as positive control are 17.43μg/ml for monophenolase and 20.69 μg/ml for diphenolase. The stem extract then separated with silica gel column chromatography and preparative thin layer chromatography. The results showed that component with Rf 0,25 and 0.63 (TLC analysis with stationary phase silica gel GF254 and mobile phase ethyl acetic: methanol (8:2)) are the marker components as tyrosinase inhibitor for X. granatum.